HLA-linked congenital adrenal hyperplasia results from a defective gene encoding a cytochrome P-450 specific for steroid 21-hydroxylation. - White, P C (1984)
We have determined the molecular genetic basis of congenital adrenal hyperplasia due to 21-hydroxylase (21-OHase) deficiency. This common disorder of cortisol biosynthesis is HLA-linked. The haplotype HLA-(A3);Bw47;DR7 is strongly associated with 21-OHase deficiency and always carries a null allele at the locus encoding the C4A (Rodgers) form of the fourth component (C4) of complement. It seemed likely that this haplotype carries a deletion encompassing the genes encoding both C4A and 21-OHase. We hypothesized that the HLA-linked defect involved a structural gene for the adrenal microsomal cytochrome P-450 specific for steroid 21-hydroxylation. Using a plasmid with a 520-base-pair bovine adrenal cDNA insert encoding the middle third of the cytochrome P-450 polypeptide, we compared hybridization patterns in DNA from normal and 21-OHase-deficient individuals. Normal human DNA yielded two fragments that hybridized with the probe after digestion with either restriction endonuclease EcoRI [12- and 14-kilobase (kb) fragments] or Taq I (3.7 and 3.2 kb). One of these bands (the first mentioned in each digest) was absent in DNA from a cell line derived from a patient homozygous for HLA-Bw47. DNA from six unrelated patients homozygous for 21-OHase deficiency who were heterozygous for HLA-Bw47 yielded diminished relative intensity of the 3.7-kb Taq I band in five patients, consistent with a heterozygous deletion, and complete disappearance of the 3.7-kb band in one. This deletion segregated with HLA-Bw47 in a large pedigree carrying 21-OHase deficiency and HLA-Bw47. Thus, 21-OHase deficiency sometimes results from the deletion of a specific cytochrome P-450 gene and sometimes, presumably, from smaller mutations. This gene is probably located very near the C4A gene.